Prevalence of Anemia among Blood Donors in Benin City: Cross-Sectional Study of Iron Status and Hematological Parameters - Fidelis Ohiremen Oyakhire; Adebukola Adisa Ekoh-Jolly; Babatunde Ishola Gabriel Adejumo; Samson Efenarhua; Osamwonyi Ernest Igbinovia (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2026)
Despite the importance of blood donation in ensuring a constant supply of blood for emergency situations and surgical procedures, frequent blood donation leads to iron depletion and anemia, posing significant health risks to donors. The study aimed to evaluate the iron status and hematological parameters among blood donors in Benin City. A cross-sectional study involving 100 blood donors was conducted across blood donation facilities in Benin City. Hematological parameters and ferritin levels were analyzed using an automated hematology analyzer (BK3100, China) and enzyme-linked immunosorbent assay (ELISA), respectively. Data were analyzed using SPSS version 26.0. Chi-square, one-way ANOVA, and Pearson correlation tests were applied, with significance set at p < 0.05. Results of the participants, 64.0% were males and 36.0% females. The self-reported prevalence of anemia was 1.0%, while all participants had hemoglobin values below WHO reference cutoffs (p<0.05). Male donors showed significantly higher hemoglobin (12.37±0.23 vs 11.05±0.17 g/dL), packed cell volume (37.43±0.60 vs 33.20±0.48%), and ferritin levels (180.23±12.79 vs 117.48±17.43 ng/mL) compared to females (p < 0.05). Conversely, white blood cell and platelet counts were significantly higher in females (p < 0.05). No significant differences were observed across age groups and donation frequencies. Blood donation frequency showed weak negative, non-significant correlations with hemoglobin, packed cell volume, and ferritin levels (p > 0.05). Conclusion Despite the prevalence found in this study, these findings underscore the need to monitor hematological parameters and ferritin levels in blood donors, particularly among women, to ensure donor health and maintain a safe and adequate blood supply.